O papel da empresa no combate à violência doméstica - Ribeiro, Roberta Karam (2022)
The social function of the company, although not regulated in the constitutional scope, is characterized as an offshoot of the social function of property, and for this reason it is considered one of the constitutional principles of the economic order, having as its scope the dignity of the human person. In the present study, business activity is analyzed from the perspective of the constitutional principles of the economic order provided for in the Federal Constitution of 1988, in order to seek a balance between business activity and the social aspects of business activity. The search for a balance between profit and social function is also the object of the entire legal system, as seen in the Maria da Penha Law (Law No. 11.340 of 2016). Article 8 of the Maria da Penha Law brings the need to create a network to fight domestic violence and violence against women, made up of the Union, States, Municipalities, non-governmental organizations and companies. Based on the need for a coalition to combat violence, companies join the coping network with the creation of channels, programs, workshops, and the provision of legal and psychological assistance for women victims of domestic violence. The object of this study is the effective role of the company in combating domestic violence. In this section, we will examine, by way of example, the MAGAZINE LUIZA WOMEN'S CHANNEL and its functionality. Thus, this text aims to outline a study on the role of the company in combating violence against women, demonstrating that with goodwill it is possible to act with dignity, in the search for a balance between profit and social interests, especially in issue of domestic violence, thus reaching the fullness of the principle of human dignity.